Cynical hostility as a determinant of toothbrushing frequency and oral hygiene - Hanna-Leena Mettovaara (Blackwell Synergy, 2006)
Aim: Our aim was to investigate whether cynical hostility, self-reported toothbrushing frequency and objectively assessed levels of oral hygiene were associated. Material and Methods: The present study sample consisted of 4156 30–64-year-old dentate Finns. The questionnaire and the home interview included information about socioeconomic and sociodemographic factors and behavioural variables, such as toothbrushing frequency, dental attendance, smoking and cynical hostility. The level of oral hygiene was assessed during a clinical oral examination. The w2 test and ordinal logistic regression analyses were used. Results: After controlling for sociodemographic and socioeconomic factors, smoking habits and reported dental attendance, the subjects belonging to the lowest cynical hostility level were found to brush their teeth significantly more often and to have better oral hygiene compared with those belonging the highest cynical hostility level. Toothbrushing frequency was adjusted when oral hygiene was used as the outcome variable. The association of cynical hostility with toothbrushing frequency and the oral hygiene seems to be partly dependent on the level of education. Conclusions: Cynical hostility is a psychosocial risk marker for the frequency and quality of toothbrushing and it could be a connecting trait between general health behaviour and oral health behaviour.